First Observations of Benthos and Seston from a Submersible in the Lower St. Lawrence Estuary - Syvitski, James; Silverberg, N.; Ouellet, G.; Asprey, K. (Géographie physique et Quaternaire, 1983)
ABSTRACTSix dives with the submersible PISCES IV have permitted a unique description of the benthic and pelagic environments of a large, deep Canadian estuary. The estuarine floor and continental slopes are divided into five depth-dependent benthic zones. In order of decreasing depth are the Bathyal Trough Zone, the lnfaunal Zone, the Ophiura Zone, the Ice Rafting Zone and the Wave Base Zone. The zonal boundaries are based on changes in the faunal community, sediment texture, current energy, level of bioturbation and suspended particulate loading. Biological resuspension appears important in the Bathyal Trough and lnfaunal Zones. Current resuspension dominates the Ophiura and Ice Rafting Zones with storm waves additionally reworking the Wave-Base sediments. Seston characteristics are strongly influenced by the source and dynamics of the host water mass. The Surface Layer, the entrained outflow from the St. Lawrence River, is the source of most suspended matter found beneath. Large particles, mostly organo-mineral aggregates, become even larger with depth and indicate a rapid downward transfer of suspended sediment. The upper Intermediate Layer is complicated by stratified zones of turbulence that temporarily reduce the floe size. With the absence of such fine water structure, the lower Intermediate Layer is characterized by long chains of marine "snow" joined by delicate filaments. The Bottom Layer, a zone of increased turbulence, had aggregates breaking up into a haze of fine particles.